THE ROLE OF YOUTH ORGANIZATIONS AS A POLITICAL EDUCATION MEANS IN IMPROVING YOUTH POLITICAL PARTICIPATION IN 2018 REGIONAL ELECTION IN BANDUNG CITY - Dadan Rizwan Fauzi (JIPIS, 2019)
ABSTRACTThis study tried to explain the role of interest groups, as one component of the political system in Indonesia. The research questions in this studyare how the regeneration mechanism was carried out by Youth Organizations in the process of political education as an effort to improve youth political participation in the 2018 regional election in Bandung, what programs were carried out by Youth Organizations in the process of political education as an effort to increase youth political participation in the 2018 regional election in Bandung, how the success of the Youth Organization program in the process of political education as an effort to improve youth political participation in the 2018 regional election in Bandung was, what obstaclesfaced by Youth Organizations in efforts to improve youth political participation in the 2018 regional election in Bandung were, how the efforts of the Youth Organization to overcome the obstacles faced in increasing youth political participation in the 2018 regional election in the city of Bandung were. In this study, the Grand Theory of Robert Brownhill and Patrice Smart was used regarding political education. The approach of this research was qualitative with a case study method. Primary data collection wascarried out technically through observation, and in-depth interviews. While secondary data collection was carried out through extensive documentary data analysis.Keywords: Youth Organization, KNPI, Political Education, Youth Political ParticipationABSTRACT  This study tried to explain the role of interest groups, as one component of the political system in Indonesia. The research questions in this studyare how the regeneration mechanism was carried out by Youth Organizations in the process of political education as an effort to improve youth political participation in the 2018 regional election in Bandung, what programs were carried out by Youth Organizations in the process of political education as an effort to increase youth political participation in the 2018 regional election in Bandung, how the success of the Youth Organization program in the process of political education as an effort to improve youth political participation in the 2018 regional election in Bandung was, what obstaclesfaced by Youth Organizations in efforts to improve youth political participation in the 2018 regional election in Bandung were, how the efforts of the Youth Organization to overcome the obstacles faced in increasing youth political participation in the 2018 regional election in the city of Bandung were. In this study, the Grand Theory of Robert Brownhill and Patrice Smart was used regarding political education. The approach of this research was qualitative with a case study method. Primary data collection wascarried out technically through observation, and in-depth interviews. While secondary data collection was carried out through extensive documentary data analysis.Keywords: Youth Organization, KNPI, Political Education, Youth Political Participation